2018
DOI: 10.14744/ejmo.2018.74745
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Vascular Endothelial Growth Factor (VEGF) and Tissue Necrosis Factor Alpha (TNFα) by the Ethanol Stem Bark Extract of Boswellia dalzielli H Attenuates Ethanol Induced Gastric Ulcer in Albino Rats.

Abstract: Objectives:The modulation of vascular endothelial growth factor, antioxidants, and tissue necrosis factor alpha (TNF-α) using ethanol stem bark extract of Boswellia dalzielii H. was evaluated in an ethanol-induced gastric ulcer albino rat model. Methods: Thirty albino rats of either sex (200-250 g) were starved for 48 h but were allowed drinking water with 8% sucrose to avoid dehydration. The rats were placed on wire gauze above the base of the cage to prevent coprophagy. At the end of the fasting period, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…We established a GU disease model in rats by gavage with anhydrous ethanol and constructed a classic GU injury model ( 23 , 24 ). Research has shown that stimulation with anhydrous ethanol (1 mL/200 g) leads to severe pathological changes in the gastric mucosa of rats, confirming that the construction of the GU model in this experiment was consistent with previous reports ( 15 , 25 , 26 ). The results of this study indicated that the intervention in anhydrous ethanol-induced GU with GYZXG was associated with changes in the levels of inflammatory and growth factors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We established a GU disease model in rats by gavage with anhydrous ethanol and constructed a classic GU injury model ( 23 , 24 ). Research has shown that stimulation with anhydrous ethanol (1 mL/200 g) leads to severe pathological changes in the gastric mucosa of rats, confirming that the construction of the GU model in this experiment was consistent with previous reports ( 15 , 25 , 26 ). The results of this study indicated that the intervention in anhydrous ethanol-induced GU with GYZXG was associated with changes in the levels of inflammatory and growth factors.…”
Section: Discussionsupporting
confidence: 92%
“…The rats were administered their respective treatments by gavage twice a day, 2 mL each time, for 7 consecutive days. On the 8th day, after fasting for 24 h, all groups except the normal control were administered 1 mL/200 g of anhydrous ethanol by gavage to induce GUs ( 15 ). One hour later, the rats were anesthetized, and blood was collected.…”
Section: Methodsmentioning
confidence: 99%